Effective coverage of antenatal care services in post war Tigray, Northern Ethiopia: An analysis of community and health facility–based surveys - Hailay Gebretnsae; Abadi Kidanemariam Berhe; Mache Tsadik; Akeza Awealom Asgedom; Mengistu Hagazi Tequare; Gebregziabher Berihu Gebrekidan; Gebru Hailu Redae; Tedros Bereket; Gebrekiros Gebremichael Meles; Mohamedawel Mohamedniguss Ebrahim; Yemane Berhane Tesfau; Gebremedhin Gebreegziabher Gebretsadik; et al. (PLoS ONE, 2025)
Background Although promoting high–quality care is particularly important in post–conflict settings, little is known about the effective coverage of antenatal care (ANC) services in post war Tigray. Thus, our study was aimed to assess the effective coverage of ANC services in post war Tigray, Northern Ethiopia. Methods A combined community and health facility–based cross–sectional study design was conducted in 24 randomly selected districts of Tigray, Northern Ethiopia from 29/01/2024–26/02/2024. Using multi–stage cluster sampling method, 2340 mothers of children under one year, 32 health facilities and 250 antenatal care (ANC) clients from the selected health facilities were included in the study. A pre–tested and structured questionnaire was used to collect the households’ data. Additionally, checklists were used to collect data on facility readiness and process quality. Data were collected by Open Data Kit (ODK) and analyzed using SPSS version 27. The effective coverage of antenatal care (ANC) services was analyzed among the target group of women by computing the proportion who received four or more ANC visits multiplied by the average facility readiness score, received iron–folate supplementation, and the average process quality score. Results In this study, 87.4% (95% Confidence Interval (CI): 86.1–88.8%) of women received their first antenatal care visit. However, only 10.7% (95% CI: 9.5–12.0%) of the women had their first visit before 12 weeks of gestation and the coverage of fourth and more ANC visits was 15.7% (95% CI: 14.2–17.2%). The overall ANC service readiness mean score was 55.6% (95%CI: 45.8–65.4%). Input–and intervention–adjusted ANC coverage was 8.7% and 7.1% respectively. The mean process quality score was 53.8% (95%CI: 51.0–56.6%), and the overall effective ANC coverage was 3.8%. Conclusions The effective coverage of ANC services in post war Tigray is very low. To improve ANC uptake and ensure that pregnant women complete the recommended number of visits, it is crucial to enhance facility readiness by equipping essential ANC tracer items in conflict–affected Tigray region. Additionally, on-the-job training for healthcare providers working in maternal and neonatal departments is crucial to reinforce the basic components of ANC services and ensure adherence to standard protocols for delivering high quality of ANC services. Promoting early ANC initiation at health posts and encouraging pregnant women to maintain continuity in their ANC visits at nearest health centers/hospital are also vital for improving ANC4 + coverage and overall effective coverage of ANC services.